Implementation of Link Failover on Metronet Network PT. Telkom Indonesia (Persero) Based on Ipv4 and OSPF - Yosy Rahmawati; Nabila Mutiara Anjani (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2023)
Metro ethernet is a data communication network owned by PT. Telkom Indonesia (Persero) through distribution channels, one of which is Open Shortest Path First (OSPF). As technology develops, IPv4 is used as the core addressing protocol for every communicating network device and has the responsibility of finding the route taken by packets to reach their destination. The problem that occurs in the data communication network is the absence of stable connectivity when there are links between cities experiencing downtime, resulting in several link congestion on the data packet path. To overcome the above problems, this study analyzed IPv4-based metro ethernet networks through the OSPF routing protocol using Graphical Network Simulator-3 (GNS-3). This study implements a failover system as a backup link in the event of a Jakarta-Bogor downlink. Based on the simulation and test results, the failover link shows a success status and functions to minimize network connection breakdowns. This is because the use of OSPF routing isOSPF routing canen the main link is down, so the path will be diverted via the backup link. QoS measurements using a single link obtained an average throughput of 195 Kbps, while dual links obtained an average throughput of 258 Kbps. This is because the distance from the source to the destination router is passed by more single links than dual links. Overall, the measurement shows that having a backup link can increase the stability of the data communication network connection when it is down and tested according to ETSI standards